Kemampuan Berpikir Matematis (Matematichal Thinking) Pustakawan Dalam Kegiatan Organisasi Informasi - Wisna Romdona; Winoto, Yunus (Nusantara Journal of Information and Library Studies (N-JILS), 2023)
The ability to think mathematically and logically in the world of libraries, especially for librarians who carry out library information organization, has not been widely discussed. In fact, these skills are very essential and fundamental to be mastered by everyone, in this case for librarians. By having a good ability in mathematical thinking, our cognitive function will also increase. Skills such as reasoning, systematic thinking, reading comprehension, problem solving will be further honed as our mathematical and logical thinking skills increase. By mastering this ability, in the end it will also increase user satisfaction.